I spy Fly Guy! - Arnold, Tedd. (New York : Scholastic, 2009)
While playing hide-and-seek with Buzz, Fly Guy is taken away by a garbage man.
"Cartwheel Books."
004-008.
320
Accelerated Reader AR
Keywords: Flies -- Juvenile fiction; Hide-and-seek -- Juvenile fiction